Assessing emotions conveyed and elicited by patient narratives and their impact on intention to participate in colorectal cancer screening: A psychophysiological investigation. - Teresa Gavaruzzi; Michela Sarlo; Francesca Giandomenico; Rino Rumiati; Francesca Polato; Franca De Lazzari; Lorella Lotto (PLoS ONE, 2018)
In the context of colorectal cancer screening, we aimed to compare the effectiveness of different emotion-laden narratives, to investigate the specific emotions elicited at both subjective and physiological levels, and to test the effects of emotions explicitly expressed by the narrative character. Study 1 used a between-participants design comparing four conditions: relief-based narrative, regret-based narrative, control (test-uptake only) narrative, and standard invitation material (no-narrative condition). Study 2 used a mixed design, with the narrative content as a within-participants factor and whether emotions were expressed by the narrative character or not as between-participants factor. The main outcome measures were: intention to undergo testing (Studies 1 and 2), knowledge, risk perception, proportion of informed choices (Study 1), subjective emotional responses, changes in skin conductance, heart rate, and corrugator muscle activity (Study 2). In Study 1, relative to the non-narrative condition (51%), only the relief-based narrative significantly increased intention to undergo testing (86%). Relative to the standard invitation material, the narrative conditions did not decrease knowledge, alter risk perception, or decrease the proportion of informed choices. In Study 2, the relief-based narrative elicited the lowest self-reported negative affect, and received greater implicit attention, as suggested by the larger heart rate decrease. Making the emotions experienced by the narrative character explicit decreased negative affect, as indicated by the lower skin conductance and corrugator responses during reading. Our findings provide support for the use of a relief-based narrative with emotions expressed by the character in addition to the standard information material to promote colorectal cancer screening.